A Morphological Analysis of Inflectional and Derivational Morphemes in Saddam Hussein’s Victory Anniversary Speech - Sandah, Wildan Muttaqiin; Djauhari, Otong Setiawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Morphology is a key area of linguistics that examines the formation of words and grammatical constructions via morphemes. This research seeks to examine the utilization of inflectional and derivational morphemes in Saddam Hussein's Victory Anniversary Speech through the lens of Laurie Bauer's (2003) morphological theory. The research utilized a qualitative descriptive approach through document analysis. The information included words with inflectional and derivational morphemes gathered from the speech transcript. The data were recognized, categorized, and examined according to the types of inflectional and derivational morphemes, and the results were interpreted with the aid of pertinent morphological theories and earlier research. The findings show that inflectional morphemes prevail over derivational morphemes, suggesting that the language mainly depends on grammatical changes to deliver clear and cohesive messages. Of the inflectional morphemes, plural markers appear most often, whereas the formation of verbs into nouns and the suffixes -tion/-ion represent the most productive derivational patterns. These results show that inflectional morphemes aid in grammatical correctness, while derivational morphemes enhance lexical diversity and reinforce political arguments. This research enhances morphological studies by showing how morphological processes facilitate efficient communication in political speeches.